Neuvermessung der Datenökonomie - Straubhaar, Thomas (Edition HWWI, 2021)
The coronavirus has questioned many old principles. This also applies to the measurement of economic activities. Methods from the heyday of industrialisation no longer fit to the structural change, first towards a service society, later towards a digital economy and now towards a data economy. A reorientation is urgently needed. This is the focus of this book. The first part deals with the extent to which the current measurement of economic activities - i.e. in particular the gross domestic product and productivity data derived from it - is accompanied by problems that lead to analytical errors in diagnosing and forecasting economic developments. The second part provides an overview of new empirical approaches that can be used to better capture what is happening in the (data) economy.